Peran Gembala Sidang Dalam Mengkaderisasi Istri Bagi Kepemimpinan Gereja Lokal - Anatje Ivone Sherly Lumantow; Simon Simon (IAKN TORAJA, 2021)
Abstract: This study departs from the factual event that the pastor's wife refused to continue the transition of the pastor's leadership in the local church. The refusal of the shepherd's wife to replace the husband as the leader of the congregation has to do with self-capacity, likes and dislikes by disapproving persons. Based on these events, this topic wants to outline how the role of the pastor of the congregation in the wiring of the wife to prepare to become a leader, in the event of a leadership transition. This paper uses qualitative methods with a literary approach accompanied by indirect interviews. The description in this article suggests, the shepherd can make efforts to care for the wife by preparing and encouraging the wife to reach a qualified academic level. Another catheterization effort that can be made by the pastor of the congregation is to give a stage in pastoral ministry, and train the wife's skills to form leadership in her. By doing the wiring as a form of preparing the wife to be a leader in the event of a leadership transition in the local church. The coding was also done by the apostle Paul to the women, so that the early church grew wider because of the role of women who became leaders in the ministry. Keywords: Cadreization, Ministry, Pastor of the Church, Women. Abstrak: Kajian ini berangkat dari peristiwa faktual bahwa adanya istri gembala yang ditolak untuk melanjutkan transisi kepemimpinan gembala sidang di gereja lokal. Penolakan istri gembala untuk menggantikan suami sebagai pemimpin jemaat berkaitan dengan kapasitas diri, like dan dislike oleh oknum yang tidak menyetujui. Berdasarkan peristiwa tersebut, topik ini hendak menguraikan bagaimana peran gembala sidang dalam pengkaderisasian istri untuk persiapan menjadi pemimpin, andai terjadi transisi kepemimpinan. Tulisan ini menggunakan metode kualitatif dengan pendekatan literatur disertai wawancara bersifat tidak langsung. Uraian pada artikel ini mengemukakan, gembala dapat melakukan upaya kaderisasi kepada istri dengan cara mempersiapkan dan mendorong istri mencapai jenjang akademik yang mumpuni. Upaya kaderisasi lain yang dapat dilakukan oleh gembala sidang adalah dengan memberi panggung dalam pelayanan pastoral, serta melatih ketrampilan istri untuk membentuk kepemimpinan dalam dirinya. Dengan melakukan pengkaderisasian itu sebagai wujud mempersiapkan istri menjadi pemimpin bila terjadi transisi kepemimpinan di dalam gereja lokal. Pengkaderisasian pun dilakukan oleh rasul Paulus kepada para perempuan-perempuan, sehingga gereja mula-mula semakin berkembang luas karena adanya peran para perempuanyang menjadi pemimpin dalam pelayanan. Kata Kunci: Gembala Sidang, Kaderisasi, Pelayanan, Perempuan.